2009
DOI: 10.1007/s00276-009-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo and in vivo coronary ostial locations in humans

Abstract: Purpose Knowledge of the normal in vivo distribution and variation of coronary ostial locations is essential in the planning of various interventional and surgical procedures. However, all studies to date have reported the distribution of coronary ostia locations only in cadaver hearts. In this study, we sought to assess the distribution of coronary ostial locations in patients using cardiac dual-source computed tomography (CT) and compare these values to those of human cadaveric specimens. Methods Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
(29 reference statements)
0
16
2
1
Order By: Relevance
“…Sudden death also has been reported which is mainly due to impairment in the diastolic coronary artery flow. Knight et al (6) has found the mean ostial positions in relation to the aortic annulus were 17 mm and 15.3 mm for the right and left coronary ostia respectively (whereas in our study, it is 18 mm-right and 17 mm-left).…”
Section: Discussioncontrasting
confidence: 47%
“…Sudden death also has been reported which is mainly due to impairment in the diastolic coronary artery flow. Knight et al (6) has found the mean ostial positions in relation to the aortic annulus were 17 mm and 15.3 mm for the right and left coronary ostia respectively (whereas in our study, it is 18 mm-right and 17 mm-left).…”
Section: Discussioncontrasting
confidence: 47%
“…5 The measurement of annulus to coronary ostia distance on 2D planes derived from volume data, such as CT, has shown discrepancy with ex vivo measurements. 18 This may be because of the differing 2D techniques (Figure VI in online-only Data supplement), which emphasizes the advantage of direct 3D measurement used in our study. The minimal distance between the leaflet tips and coronary ostia can also be measured that may help predict potential complications of calcium embolization during transcatheter AV replacement.…”
Section: Discussionmentioning
confidence: 95%
“…Both circular and eccentric orifices were constructed such that the cross-sectional orifice areas were the same. Aortic annulus models were mated with a custom-built idealized acrylic aortic root model based on clinical measurements [27,28] consisting of a straight rigid ascending aorta section developing into an axisymmetric sinus region (figure 2a,b). Valve deployment was carried out as per the instructions of use.…”
Section: Valve and Aortic Root Modelmentioning
confidence: 99%